Defending the Doctorate: Three PhD Graduates’ Narrated Experiences of Dissertation Oral Examinations - Yulhenli Thabran (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
The dissertation defense is one of the most consequential yet comparatively underexplored stages of doctoral education. Although existing research has largely focused on examination procedures, assessment practices, and institutional regulations, less attention has been paid to how doctoral candidates experience and interpret the defense, particularly in the Indonesian context. This study explores the experiences of three doctoral graduates who successfully completed their dissertation oral examinations at a public university in Indonesia. Guided by narrative inquiry and informed by Mertova and Webster’s (2020) Critical Event Narrative Analysis (CENA), the study examines how participants narrated and made meaning of their experiences before, during, and after the defense. Data were generated through semi-structured narrative interviews and analyzed through narrative reconstruction, critical-event analysis, and cross-narrative thematic comparison within Clandinin and Connelly’s (2000) dimensions of temporality, sociality, and place. The findings revealed three interconnected themes: Anticipating the Defense: Between Anxiety and Hope, Negotiating the Defense: Academic Authority, Language, and Identity, and Becoming a Doctor: Relief, Recognition, and Transformation. Before the defense, participants navigated anxiety and uncertainty through preparation and support from supervisors and family members. During the examination, they negotiated academic authority, language, and scholarly identity while responding to expert evaluation. Following successful completion, they experienced relief, recognition, increased confidence, and changing understandings of themselves as scholars. The findings highlight the dissertation defense as a critical event whose significance extends beyond formal assessment to encompass emotional, relational, and identity-related dimensions of doctoral development. By foregrounding doctoral graduates’ voices, the study contributes to research on doctoral education by illuminating how dissertation defenses are experienced, interpreted, and incorporated into emerging scholarly identities in an Indonesian context.